(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
One important factor is the involvement provided by social workers, who help married women by creating individualized support systems. Seminars, mentorship programs, and counseling services that focus on stress reduction, time management, and communication skills should all fall under this umbrella. The development of a mutually beneficial work environment is another important outcome of social group work. Married women may find a safe space here to talk about their lives, get advise from one another, and make connections that will help them in the long run. Evaluate married women’s work-life balance in the workplace in this article.